The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fped.2016.00089
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in Critically Ill Children with Respiratory Failure

Abstract: This article discusses the rationale of sedation in respiratory failure, sedation goals, how to assess the need for sedation as well as effectiveness of interventions in critically ill children, with validated observational sedation scales. The drugs and non-pharmacological approaches used for optimal sedation in ventilated children are reviewed, and specifically the rationale for drug selection, including short- and long-term efficacy and safety aspects of the selected drugs. The specific pharmacokinetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 150 publications
0
51
0
20
Order By: Relevance
“…opioids and benzodiazepines). Although we did not analyze potential symptoms of withdrawal or withdrawal prevention management (for Review on weaning treatment, see [26]), we confirmed that extended administration of opioids and benzodiazepines was indicated specifically for weaning management as per primary team and/or pain service consult notes. In this pilot case report, subjects were categorized and named as Preterm 1, 2, 3 and Term 1, 2, 3 in order of increasing corrected age at time of post-Foker MRI scan.…”
Section: Study Design and Subjectsmentioning
confidence: 81%
“…opioids and benzodiazepines). Although we did not analyze potential symptoms of withdrawal or withdrawal prevention management (for Review on weaning treatment, see [26]), we confirmed that extended administration of opioids and benzodiazepines was indicated specifically for weaning management as per primary team and/or pain service consult notes. In this pilot case report, subjects were categorized and named as Preterm 1, 2, 3 and Term 1, 2, 3 in order of increasing corrected age at time of post-Foker MRI scan.…”
Section: Study Design and Subjectsmentioning
confidence: 81%
“…opioids and benzodiazepines). Although we did not analyze potential symptoms of withdrawal or withdrawal prevention management (for Review on weaning treatment see (Vet et al, 2016)), we confirmed administration of opioids and benzodiazepines was indicated specifically for weaning management as per primary team and/or pain service consult notes. Representative timeline illustrating sequence of perioperative critical care was presented elsewhere (Hodkinson et al, 2019; Mongerson et al, 2019).…”
Section: Methodsmentioning
confidence: 96%
“…Patients' eligibility criteria were: full-term (37 to 42 weeks GA at birth) and moderate-to-late preterm (28 to 36 weeks GA at birth) patients <1 year gestation-corrected age that underwent surgery for Foker process for LGEA repair 1,22 . We selected infants that required prolonged postoperative sedation (≥5 days) associated with development of pharmacological dependence to drugs of sedation 11,[23][24][25] . Representative timeline illustrating sequence of perioperative critical care was presented previously 6,26 .…”
Section: Methodsmentioning
confidence: 99%